Concepções dos estudos de usuários na visão dos professores dos cursos de Biblioteconomia brasileiros - Costa, Maria de Fátima Oliveira [UNESP] (2014)
The concepts of user studies, their discussion and dissemination through teaching is the subject matter approached in this thesis to make clear how they are identified and analyzed by the professors who teach this discipline in Librarianship courses in Brazilian universities. Through them, to know how they are being worked on in the classroom, their dialogues with other areas and with the theoreticians who permeate the scientific production in the context of librarianship teaching. It aims to identify and analyze these concepts and how they are perceived, exposed, assimilated and reproduced in the teaching practice. It shows a national panorama represented by those courses that participated in the survey with the intention of rethinking and examining how the issue has been developed within Information Science. Some researchers have strengthened underlying theoretical support of studies in the field of Information Science, the approaches described, preferably by Brenda Dervin, Ellis, Wilson, Khulthau, Choo, Araújo, Figueiredo and Ferreira; in the reading of book chapters , journal articles and dissertations as well as doctoral theses on the subject , which stood in the state of art in the object of study . We define as a methodological approach the content analysis according to Bardin, conducting a qualitative descriptive research. It was required to the teachers in question, initially, plans to teach the subject with its various components and secondly, the questionnaire. The latter was divided into two parts, being one of them with the characterization of the teacher and the other one with nine open questions on teaching issues. It was assigned a pretest of the questionnaire when it was found to be necessary to modify some questions, immediately redone. The lesson plans were examined, together with the responses of the questionnaires and from the concepts expressed by the professors, as the constituent items of the...